(untitled) (Journal of Philosophy Culture and Political Science, 2022)
In the article, the authors investigated the main approaches to the study of protest factors and their features. Based on quantitative and qualitative methods identified the main factors and causes of protests in Kazakhstan. A number of questions of the sociological research are aimed at assessing the respondents’ economic situation in the country, the financial situation and consumer potential of their family, identifying the problems facing the country. Another set of questions focused on identifying the level of trust in the media, determining the degree of influence of social networks on protest activity, assessing the level of protest of the population. The results of a survey of 2 000 respondents and the study of data from 16 focus group discussions in Kazakhstan revealed a hierarchy of factors affecting the protest potential in the country. The protest potential of Kazakhstan’s society is primarily associated with socio-economic problems. In addition, inefficient public administration and corruption are a factor of protest. This article examines the degree of readiness of Kazakhstanis to participate in protest actions. The propensity to participate in protests has been studied in ethnic, educational and sample of regions. The degree of impact of mass media on the protest potential of the Kazakh society is revealed. Key words: protest potential, protest activity, sample of regions, factors, conflict.